Międzynarodowe doświadczenia z praktycznym wykorzystaniem strategicznej karty wyników - Skrzypek, Piotr (International experience in practical usage of balanced scorecard, 2006)
The Balanced Scorecard was originally designed as a measurement of performance system. Since then it has transformed into a new strategic management control system, which helps implement the company’s strategy. For the last thirteen years this tool has been implemented in hundreds of companies over the world. Nowadays a great deal of research work on this issue has been published. As a result the cross-sectional analysis is can be carried out. This paper describes the conclusion from these studies bringing piece of information about practical usage of BSC.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 276-287